Environmental exposure to perchlorate, nitrate, and thiocyanate in relation to biological aging in U.S. adults, a cross-sectional NHANES study - Kong, Weiliang; Jin, Yina (Frontiers in Public Health, 2025)
BackgroundFew studies have investigated the associations between perchlorate, nitrate, and thiocyanate (PNT) and biological aging. This study aimed to assess the association between PNT and biological aging among U.S. adults.MethodsUtilizing multivariable linear regression and restricted cubic splines (RCS), we analyzed urinary PNT levels’ impact on phenotypic age and biological age. Subgroup and sensitivity analyses were also conducted. Weighted Quantile Sum (WQS) and Bayesian Kernel Machine Regression (BKMR) models examined PNT mixtures.Results8,368 participants were analyzed. Mean phenotypic age was 43.05 ± 0.48 years, mean biological age was 47.08 ± 0.4 years. Multivariable linear regression showed significant negative associations between higher PNT levels and phenotypic age (perchlorate β = −0.6, 95% CI: −0.93 to −0.27; nitrate β = −0.81, 95% CI: −1.19 to −0.42; thiocyanate β = −0.56, 95% CI: −0.77 to −0.34) after covariates adjusted. RCS demonstrated negative nonlinear relationships between PNT exposure and phenotypic age (nonlinear p values: 0.002, <0.001, and <0.001), with stable results in sensitivity analyses. Nitrate exposure showed a significant negative association with biological age (β = −0.78, 95% CI: −1.13 to −0.44), indicating a consistent negative linear relationship observed through RCS and remaining stable across sensitivity analyses. WQS regression revealed a negative association between the mixture and phenotypic age in both positive and negative directions, with a significant negative association with biological age in the negative direction. BKMR analysis revealed a negative association between PNT mixtures and phenotypic age, with nitrate and thiocyanate identified as the primary predictors of phenotypic age. No association found between PNT mixture and biological age.ConclusionIndividual or combined PNT are negatively associated with phenotypic age. High nitrate is associated with reduced biological age, showcasing consistent outcomes.